Adding a single low-dose of primaquine (0.25 mg/kg) to artemether-lumefantrine did not compromise treatment outcome of uncomplicated Plasmodium falciparum malaria in Tanzania: a randomized, single-blinded clinical trial. (December 2016) - Mwaiswelo, Richard; Ngasala, Billy; Jovel, Irina; Aydin-Schmidt, Berit; Gosling, Roland; Premji, Zul; Mmbando, Bruno; Björkman, Anders; Mårtensson, Andreas
Abstract Background The World Health Organization (WHO) recently recommended the addition of a single low-dose of the gametocytocidal drug primaquine (PQ) to artemisinin-based combination therapy (ACT) in low transmission settings as a component of pre-elimination or elimination programmes. However, it is unclear whether that influences the ACT cure rate. The study assessed treatment outcome of artemether-lumefantrine (AL) plus a single PQ dose (0.25 mg/kg) versus standard AL regimen for treatment of acute uncomplicatedPlasmodium falciparum malaria in Tanzania. Methods A randomized, single-blinded, clinical trial was conducted in Yombo, Bagamoyo district, Tanzania. Acute uncomplicatedP. falciparum malaria patients aged ≥1 year, with the exception of pregnant and lactating women, were enrolled and treated with AL plus a single PQ dose (0.25 mg/kg) or AL alone under supervision. PQ was administered together with the first AL dose. Clinical and laboratory assessments were performed at 0, 8, 24, 36, 48, 60, and 72 h and on days 7, 14, 21, and 28. The primary end-point was a polymerase chain reaction (PCR)-adjusted adequate clinical and parasitological response (ACPR) on day 28. Secondary outcomes included: fever and asexual parasitaemia clearance, proportion of patients with PCR-determined parasitaemia on day 3, and proportion of patients withPf mdr1 N86Y andPf crt K76T on days 0, 3 and day of recurrent infection. Results Overall 220 patients were enrolled, 110 were allocated AL + PQ and AL, respectively. Parasite clearance by microscopy was fast, but PCR detectable parasitaemia on day 3 was 31/109 (28.4 %) and 29/108 (26.9 %) in patients treated with AL + PQ and AL, respectively (p = 0.79). Day 28 PCR-adjusted ACPR and re-infection rate was 105/105 (100 %) and 101/102 (99 %) (p = 0.31), and 5/107 (4.7 %) and 5/8 (4.8 %) (p = 0.95), in AL + PQ and AL arm, respectively. There was neither any statistically significant difference in the proportion ofPf mdr1 N86Y orPf crt K76T between treatment arms on days 0, 3 and day of recurrent infection, nor within treatment arms between days 0 and 3 or day 0 and day of recurrent infection. Conclusion The new WHO recommendation of adding a single low-dose of PQ to AL did not compromise treatment outcome of uncomplicatedP. falciparum malaria in Tanzania. Trial registration number NCT02090036